Prediction of the long-term efficacy of STA-MCA bypass by DSC-PI - Hui Li (De Gruyter, 2016)
Superficial temporal artery-middle cerebral artery (STA-MCA) bypass [1,2] is an important and effective type of surgical revascularization that is widely used in the treatment of ischemic cerebral artery disease. However, a means of predicting its postoperative efficacy has not been established [3,4]. The present study analyzes the correlation between preoperative perfusion parameters (obtained using dynamic susceptibility contrast-enhanced perfusion imaging, DSC-PI) and postoperative long-term prognosis (using modified Rankin Scale, mRS scores). The preoperative perfusion parameters were defined by a combination of perfusion-weighted imaging and the Alberta Stroke Program Early Computerized Tomography Score (PWI-ASPECTS) and included cerebral blood flow (CBF)-ASPECTS, cerebral blood volume (CBV)-ASPECTS, mean transit time (MTT)-ASPECTS, and time to peak (TTP)-ASPECTS. Preoperative and postoperative scores were determined for 33 patients that received a unilateral STA-MCA bypass in order to discover the most reliable imaging predictive index as well as to define the threshold value for a favorable clinical outcome. The results showed that all of the PWI-ASPECTS scores were significantly negatively correlated with clinical prognosis. Receiver operating curve (ROC) analysis of the preoperative parameters in relation to long term prognosis showed the area under curve (AUC) was maximal for the CBF-ASPECTS score (P = 0.002). A preoperative score of less than six indicated a poor postoperative prognosis (sensitivity = 74.1%, specificity = 100%, AUC = 0.843). In conclusion, preoperative PWI-ASPECTS scores have been found useful as predictive indexes for the long-term prognosis of STA-MCA bypass patients, with higher scores indicating better postoperative long-term outcomes. As the most valuable prognostic indicator, the preoperative CBF-ASPECTS score has potential for use as a major index in screening and outcome prediction of patients under consideration for STA-MCA bypass surgery.